OPTIMALISASI KEMAMPUAN MOTORIK HALUS SISWA MELALUI MEDIA KINETIC SAND DI TK BAHRUL ULUM BANGOREJO BANYUWANGI - Jon Iskandar Bahari; Umi Nurul Hamidah (Tarbiyatuna Kajian Pendidikan Islam, 2022)
The purpose of this study is to optimize students' fine motor skills during the covid-19 pandemic and through kinetic sand media and know supporting factors and inhibitors in optimizing students' fine motor skills during the covid-19 pandemic through kinetic sand media in Bahrul Ulum Kindergarten Purwodadi Village Bangorejo Banyuwangi Regency. This type of research uses descriptive qualitative research. The objects of this research are the principal, class A teacher, group A student and student guardian at Bahrul Ulum Kindergarten Purwodadi Village Bangorejo District Banyuwangi. Research data is collected through observation methods, documentation, and interviews. Data analysis techniques use the Miles and Huberman models. As for the validity of the data using The Triangulation Source. The result of this research is to optimize students' fine motor skills through kinetic sand media in the pandemic period as follows: 1) planning: a teacher must involve the student guardian to the maximum especially in the pandemic period, especially in planning learning (RPPH and RPPM), 2) implementation: the teacher must explain to the student guardian regarding the mentoring process so that the assistance carried out by the student guardian can be maximized, 3) Evaluation can be carried out during learning by preparing instructions. The supporting factors in this study are: antuasias guardians of students and students who are high in learning and media can be obtained easily. The inhibiting factor is that not all student guardians have a special base during media use, so during sand play will be scattered and the child is not focused during play.